2017
DOI: 10.18295/squmj.2017.17.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Bacille Calmette-Guérin Vaccine-Induced Tuberculous Hip Osteomyelitis in an Infant: Case report

Abstract: To this day, tuberculosis (TB) continues to pose a significant global health burden. The World Health Organization's Expanded Programme on Immunization (EPI) recommends the bacille Calmette-Guérin (BCG) vaccine for infants to protect against the haematogenous spread of primary TB and other more severe types of TB infection. We report an eight-month-old boy who presented to the Armed Forces Hospital, Muscat, Oman, in 2015 with a one-month history of intermittent fever associated with a limited range of motion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In contrast to these findings, other studies have shown that extremity bones, mainly the lower limbs, are more commonly involved with BCG osteomyelitis than the axial skeleton. 2 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these findings, other studies have shown that extremity bones, mainly the lower limbs, are more commonly involved with BCG osteomyelitis than the axial skeleton. 2 , 14 …”
Section: Discussionmentioning
confidence: 99%
“… 19 Patients reporting with isolated BCG osteomyelitis had an apparently normal immunological evaluation. 2 , 14 Multiple case reports have described disseminated BCG infection in children with different types of SCID including IL7R gene mutation and JAK3 deficiency. 11 , 12 , 18 Preparation SCID patients with disseminated BCG infection for transplant was a real challenge in one of our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five criteria were proposed to establish the osteitis diagnosis after BCG vaccination: BCG vaccination in the neonatal period; a period of less than 4 years between vaccination and symptom onset; no contact between the child and any adults with TB; a consistent clinical profile; and TB suggestive histopathology [4,5]. Symptoms usually occur during a period ranging from a few months to 5 years post-vaccination [6]. The symptoms are non-specific, and the diagnosis is usually delayed.…”
Section: Observationmentioning
confidence: 99%
“…Tuberculosis (TB) is an essential problem for healthcare systems especially in developing countries. TB continues to pose a significant global health burden [1]. Bacillus Calmette-Guérin (BCG) is an important vaccine used to prevent Tuberculosis (TB), especially meningeal TB and disseminated TB disease in children [2].…”
Section: Introductionmentioning
confidence: 99%